EVALUASI KEJADIAN INTERAKSI OBAT PADA PASIEN RAWAT INAP GERIATRI PENDERITA GAGAL JANTUNG - Siti Mariam (Jurnal Farmamedika (Pharmamedika Journal), 2016)
An interaction occurs when the effects of a drug changed by the presence of other drugs, herbal medicine, food, drinks or other chemical agents in the environment. Drug interactions considered clinically important when the resulting increase or decrease the toxicity and effectiveness of the drugs that interact, especially when it comes to drugs with narrow safety margin (low terapheutic window). Genesis interactions may occur in patients taking two or more drugs. Interaction incident may occur in patients taking two or more drugs. The use of many drugs that often occur in geriatric patients, who suffer from degenerative diseases such as hypertension, diabetes mellitus, dyslipidemia, osteoarthritis and cardiovascular disease. Research conducted retrosfektif using medical records (MR) geriatric patients suffering from heart failure who are hospitalized in the Betha Medika Hospital in Sukabumi period March-April 2016. Retrieved 70 patients, 45% male and 54% female. Morbidities highest of 10 comorbidities with most patients is Hypertension Heart Disease (PJH). Drud interaction occur between: spironolactone, digoxin, amlodipine, bisoprolol with other drugs medicine drug classes heart failure and comorbid disease drug interactions with the number of events is different.